NEW 1,3,4-TIADIAZOLE DERIVATIVES WITH ANTIBACTERIAL ACTIVITY - A. S. Koshevenko; V. N. Yuskovets; E. P. Ananyeva; I. P. Yakovlev; T. L. Semakova (Разработка и регистрация лекарственных средств)
The method of obtaining new heterocyclic compounds - chlorides 2-[(Z)-1-(3,5-diaryl-1,3,4-thiadiazol-2(3H)-iliden)methyl]-3,5-diaryl-1,3,4-thiadiazol-3 was developed. The structure and individuality of the obtained compounds are proved by the physico-chemical methods for the identification of organic compounds: 1Н and 13С NMR, IR spectrometry, mass spectrometry. Antibacterial activity was defined against Escherihia coli, Staphylococcus aureus, Bacillus cereus. It was shown that these compounds have a pronounced antibacterial activity against gram-positive bacteria. The most active compound has been identified, which can potentially be used in medicine as an antimicrobial agent.